Clinical study of octacalcium phosphate and collagen composite in oral and maxillofacial surgery. (January 2020) - Kawai, Tadashi; Kamakura, Shinji; Matsui, Keiko; Fukuda, Masayuki; Takano, Hiroshi; Iino, Mitsuyoshi; Ishikawa, Shigeo; Kawana, Hiromasa; Soma, Tomoya; Imamura, Eisaku; Kizu, Hideki; Michibata, Aya; et al.
Octacalcium phosphate and its collagen composite have been recognized as bone substitute materials possessing osteoconductivity and biodegradation properties. We evaluated the effectiveness of octacalcium phosphate and its collagen composite used for bone augmentation in major oral and maxillofacial surgeries in a clinical trial. Octacalcium phosphate and its collagen composite were used in cases of sinus floor elevation in 1- and 2-stage, socket preservation, cyst, and alveolar cleft procedures. A total of 60 patients were evaluated for effectiveness after the implantation of octacalcium phosphate and its collagen composite. Although sinus floor elevation in 1-stage, cyst, and alveolar cleft cases met the criteria for the judgment of success, sinus floor elevation in 2-stage and socket preservation groups did not meet the criteria in the initial evaluation. However, an additional evaluation for reconfirmation revealed the effectiveness of octacalcium phosphate and its collagen composite in those groups, and all evaluation results ultimately indicated the success of this clinical trial. Therefore, this clinical trial suggested that application of octacalcium phosphate and its collagen composite for oral and maxillofacial surgery was safe and effective and that octacalcium phosphate and its collagen composite could be a bone substitute candidate instead of autologous bone.